2014
DOI: 10.3233/fi-2014-1011
|View full text |Cite
|
Sign up to set email alerts
|

The Undecidability of the Logic of Subintervals

Abstract: The Halpern-Shoham logic is a modal logic of time intervals. Some effort has been put in last ten years to classify fragments of this beautiful logic with respect to decidability of its satisfiability problem. We complete this classification by showing -what we believe is quite an unexpected result -that the logic of subintervals, the fragment of the Halpern-Shoham logic where only the operator "during", or D, is allowed, is undecidable over discrete structures. This is surprising as this, apparently very simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…An up-to-date account of undecidability results for HS fragments can be found in [5]. Among the known results, we recall the undecidability of the logics D (quantifying over sub-intervals) and O (quantifying over overlapping intervals) -as well as of their transposes -interpreted over infinite discrete temporal domains [5,16], and the undecidability of the logic BE (quantifying over beginning and ending intervals) interpreted over both dense and infinite discrete temporal domains [12,15].…”
Section: Cone Logic and Modal Logics Of Time Intervalsmentioning
confidence: 99%
“…An up-to-date account of undecidability results for HS fragments can be found in [5]. Among the known results, we recall the undecidability of the logics D (quantifying over sub-intervals) and O (quantifying over overlapping intervals) -as well as of their transposes -interpreted over infinite discrete temporal domains [5,16], and the undecidability of the logic BE (quantifying over beginning and ending intervals) interpreted over both dense and infinite discrete temporal domains [12,15].…”
Section: Cone Logic and Modal Logics Of Time Intervalsmentioning
confidence: 99%
“…In [8], it has been shown that the satisfiability problem for HS interpreted over all relevant (classes of) linear orders is highly undecidable. Since then, a lot of work has been done on satisfiability for HS fragments, which showed that undecidability rules over them [3], [10], [13]. However, meaningful exceptions exist, e.g., the interval logic of temporal neighbourhood AA and the logic of sub-intervals D [4]- [6], [17].…”
Section: Introductionmentioning
confidence: 99%
“…They take intervals, instead of points, as their primitive temporal entities. Such a choice gives them the ability to cope with advanced temporal properties, such as actions with duration, accomplishments, and temporal aggregations, which can not be properly dealt with by standard, point-based temporal logics.Expressiveness of ITLs makes them well suited for many applications in a variety of computer science fields, including artificial intelligence (reasoning about action and change, qualitative reasoning, planning, configuration and multi-agent systems, and computational linguistics), theoretical computer science (formal verification, synthesis), and databases (temporal and spatio-temporal databases) [2,10,18,30,8,27,26,19,11]. However, this great expressiveness is a double-edged sword: in most cases the satisfiability problem for ITLs turns out to be undecidable, and, in the few cases of decidable ITLs, the standard proof machinery, like Rabin's theorem, is usually not applicable.The most prominent ITL is Halpern and Shoham's modal logic of time intervals (HS, for short) [13].…”
mentioning
confidence: 99%